2005
DOI: 10.1007/s00425-005-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ubiquitin variant ubR48 decreases proteolytic activity in Arabidopsis and induces cell death

Abstract: The ubiquitin-proteasome pathway is the major route for protein degradation in eukaryotes. We show here that this pathway can be inhibited in Arabidopsis thaliana by expression of a ubiquitin variant that contains Arg instead of Lys at position 48 (ubR48). A major consequence of ubR48 expression is the induction of cell death. Cell death induction coincides with the appearance of reactive oxygen intermediates, but is independent of salicylic acid. We found changes in expression of some defense-related genes, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…interference with targeted UPS protein degradation was comparable to SylA-mediated inhibition of the proteasome using a conditional Arabidopsis ubiquitin mutant line that over-expresses ubiquitin with a K48R substitution, which cannot form K48-linked polyubiquitylation chains (31). However, we found that the overlap was small between the accumulating proteins in both experiments (supplemental Table S8).…”
Section: Different Methods Of Interfering With the Ups Results In Diffmentioning
confidence: 71%
See 1 more Smart Citation
“…interference with targeted UPS protein degradation was comparable to SylA-mediated inhibition of the proteasome using a conditional Arabidopsis ubiquitin mutant line that over-expresses ubiquitin with a K48R substitution, which cannot form K48-linked polyubiquitylation chains (31). However, we found that the overlap was small between the accumulating proteins in both experiments (supplemental Table S8).…”
Section: Different Methods Of Interfering With the Ups Results In Diffmentioning
confidence: 71%
“…Plant Growth and Inhibition of the Proteasome-The plant material used in this study was either from Arabidopsis thaliana ecotype Col-0 (wild type) or the ubR48 mutant in which four transgenic ubiquitin proteins mutated at their K48 position can be expressed under the control of a dexamethasone (DEX)-inducible 35S promoter (31). Seeds were stratified for 2 days in darkness at 4°C and after germination, the plants were grown in short day conditions with 8 h light and 16 h darkness.…”
Section: Methodsmentioning
confidence: 99%
“…Polyubiquitination results from formation of the isopeptide bonds connecting the C-terminal glycine of the incoming ubiquitin monomer and the e-amino group of one of the seven lysine residues (K63, K48, K33, K29, K11 and K6) of ubiquitin attached to the substrate protein (Vierstra 2009, Kim et al 2013, Walsh and Sadanandom 2014. Because the K48 linkage is best known for targeting ubiquitinated proteins for degradation (Vierstra 2009, Kim et al 2013, Walsh and Sadanandom 2014, we investigated the possible involvement of the K48 linkage in the blue light-dependent CRY2 degradation by a previously reported genetics approach, the ubR48 method (Schlögelhofer et al 2006). In this experiment, the possible effect of expression of the ubR48 ubiquitin mutant, which contains arginine instead of lysine at position 48 (K48), on the blue light-dependent CRY2 degradation was examined in the transgenic plants expressing the dexamethasone (DEX)-inducible ubiquitin mutant ubR48 (Schlögelhofer et al 2006).…”
Section: Cry2 Polyubiquitination Involves K48 Linkage Of Ubiquitinsmentioning
confidence: 99%
“…The use of a ubiquitin variant containing Arg instead of Lys at position 48 (UbR48) impairs polyubiquitination, and thus proteolytic degradation, but allows monoubiquitination to occur. Expression of UbR48 in tobacco (Nicotiana tabacum) plants induced the development of necrotic lesions and altered plant responses to infection with Tobacco mosaic virus (TMV; Becker et al, 1993), whereas in Arabidopsis, expression of UbR48 led to spontaneous cell death symptoms, reactive oxygen species (ROS) production, and constitutive induction of defense-related genes (Schlögelhofer et al, 2006). However, Arabidopsis plants expressing UbR48 did not present altered resistance to virulent or avirulent Pseudomonas syringae bacterial strains (Schlögelhofer et al, 2006).…”
Section: Ubiquitin and 26s Proteasomal Componentsmentioning
confidence: 99%
“…Expression of UbR48 in tobacco (Nicotiana tabacum) plants induced the development of necrotic lesions and altered plant responses to infection with Tobacco mosaic virus (TMV; Becker et al, 1993), whereas in Arabidopsis, expression of UbR48 led to spontaneous cell death symptoms, reactive oxygen species (ROS) production, and constitutive induction of defense-related genes (Schlögelhofer et al, 2006). However, Arabidopsis plants expressing UbR48 did not present altered resistance to virulent or avirulent Pseudomonas syringae bacterial strains (Schlögelhofer et al, 2006). Partial depletion of ubiquitin levels by transient-induced silencing of the ubiquitin-encoding gene in barley (Hordeum vulgare) epidermal cells resulted in enhanced susceptibility to the powdery mildew fungus Blumeria graminis f. sp.…”
Section: Ubiquitin and 26s Proteasomal Componentsmentioning
confidence: 99%